2021
DOI: 10.22541/au.162591098.83705488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How do genetic relatedness and spatial proximity shape African swine fever infections in wild boar?

Abstract: The importance of social and spatial structuring of wildlife populations for disease spread, though widely recognized, is still poorly understood in many host-pathogen systems. In particular, system specific kin relationships among hosts can create contact heterogeneities and differential disease transmission rates. Here, we investigate how distance-dependent infection risk is influenced by genetic relatedness in a novel wild boar ( Sus scrofa) - African swine fever (ASF) system. We hypothesized that the infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…We assumed that individuals within grid cells mixed homogenously, while groups among grid cells contacted each other at a frequency that depended on distance. We made these assumptions because previous work found that clustering of family groups influenced spatial disease transmission of the ASFv in wild pigs (Pepin et al., 2021; Podgorski et al., 2022). The force of infection (λ, Equation 1) included contact terms (ω) for within cells ( w ) and direct ( d ) or carcass‐based ( c ) transmission between cells.…”
Section: Methodsmentioning
confidence: 99%
“…We assumed that individuals within grid cells mixed homogenously, while groups among grid cells contacted each other at a frequency that depended on distance. We made these assumptions because previous work found that clustering of family groups influenced spatial disease transmission of the ASFv in wild pigs (Pepin et al., 2021; Podgorski et al., 2022). The force of infection (λ, Equation 1) included contact terms (ω) for within cells ( w ) and direct ( d ) or carcass‐based ( c ) transmission between cells.…”
Section: Methodsmentioning
confidence: 99%